2016
DOI: 10.1007/978-3-662-53536-3_14
|View full text |Cite
|
Sign up to set email alerts
|

Drawing Planar Graphs with Prescribed Face Areas

Abstract: We study straight-line drawings of planar graphs where every inner face has a prescribed area. A plane graph is area-universal if for every assignment of positive real numbers to the inner faces, there exists a straight-line drawing in which the area of each inner face equals to the assigned number. The only non-area-universal graphs known so far are those containing the octahedron graph as a subgraph.We give a simple counting argument that allows us to prove non-area-universality for a large class of triangul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Performing a diamond addition of order on some plane graph changes the degree of exactly two vertices by while all other vertex degrees remain the same. Consequently, if is even, all vertices of K have even degree, and hence, K as an Eulerian triangulation is not area-universal as shown by the author in [15,Theorem 1]. It remains to prove the area-universality of odd accordion graphs with the help of Theorem 1.…”
Section: Accordion Graphsmentioning
confidence: 96%
See 3 more Smart Citations
“…Performing a diamond addition of order on some plane graph changes the degree of exactly two vertices by while all other vertex degrees remain the same. Consequently, if is even, all vertices of K have even degree, and hence, K as an Eulerian triangulation is not area-universal as shown by the author in [15,Theorem 1]. It remains to prove the area-universality of odd accordion graphs with the help of Theorem 1.…”
Section: Accordion Graphsmentioning
confidence: 96%
“…The double stacking graph H ,k is the plane graph obtained from G by applying a diamond addition of order − 1 on Au and a diamond addition of order k − 1 on vw. If · k is odd, every plane graph in [H ,k ] is Eulerian and hence not areauniversal by [15,Theorem 1]. If · k is even, we consider an algebraically independent area assignment of H ,k , show that its last face function is crr-free and has odd max-degree.…”
Section: Double Stacking Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…The area-universal convex polygonal drawings for biconnected outer planar graphs are given in [12]. Recently, it has been shown that a planar graph G is area-universal if for any area assignment to the inner regions of G, a straight line drawing of G can be realized [13,14] and the area-universality of subgraphs of such graphs can be seen in [15]. The extension of the concept of area-universality to rectilinear duals has been given in [16,17].…”
Section: Related Workmentioning
confidence: 99%